Who cares for adolescents and young adults with cancer in Brazil? - Helena T.G. Martins; Nathalie V. Balmant; Neimar de Paula Silva; Marceli de O. Santos; Rejane de S. Reis; Beatriz de Camargo (Brazilian Society of Pediatrics, 2018)
Objective: Approximately 6% of all cancers arise in adolescents and young adults. Currently, the ward type best placed to treat this patient group remains controversial. The aim of this study was to evaluate exactly where adolescents and young adults with cancer are treated in Brazil. Methods: Data were extracted from 271 Brazilian hospital‐based cancer registries (2007-2011), including all five national regions (North, Northeast, Midwest, South, and Southeast). Variables included gender, age, ethnicity, National Code of Health Establishment, hospital unit state, and region. Tumors were classified according to the World Health Organization classification for adolescents and young adults with cancer. Odds ratios with 95% confidence intervals were computed by unconditional logistic regression. Results: Most patients were managed on medical oncology wards, followed by pediatric oncology and then by non‐specialist wards. Of patients aged 15-19 years, 49% were managed on pediatric wards; most of the older patients (96%; aged 20-24) were managed on adult wards. Patients were more likely to be seen in medical oncology wards as their age increased (OR = 2.03 [1.98-2.09]), or if they were based in the South (OR = 1.50 [1.29-1.73]). Conversely, bone tumors were less likely to be treated (decreased OR) on medical oncology wards, regardless of age, gender, and region. Conclusion: An elevated risk of treatment on medical oncology wards was observed for older patients and those treated in the South. Bone tumors were generally treated in pediatric oncology wards, while skin cancers were treated in medical oncology wards, regardless of age, gender, and region. Resumo: Objetivo: Aproximadamente 6% de todos os cânceres surgem em adolescentes e adultos jovens. Atualmente, o melhor tipo de enfermaria para tratar esse grupo de pacientes continua sendo controverso. O objetivo deste estudo foi avaliar exatamente onde os adolescentes e adultos jovens com câncer são tratados no Brasil. Métodos: Foram coletados dados de 271 registros de câncer de base hospitalar (2007‐2011), inclusive de todas as cinco regiões nacionais (Norte, Nordeste, Centro‐Oeste, Sul e Sudeste). As variáveis incluíram sexo, idade, etnia, o Código Nacional de Estabelecimento de Saúde e o estado e a região da unidade hospitalar. Os tumores foram classificados de acordo com a classificação da Organização Mundial de Saúde para adolescentes e adultos jovens com câncer. As razões de chance com intervalos de confiança de 95% foram calculadas por regressão logística incondicional. Resultados: A maioria dos pacientes foi tratada em enfermaria de oncologia médica, seguido da enfermaria de oncologia pediátrica e, então, a enfermaria sem especialidade. 49% dos pacientes entre 15‐19 anos foram tratados em enfermarias pediátricas; os pacientes mais velhos (96%, entre 20‐24) foram tratados em enfermarias de adultos. Os pacientes apresentaram maior propensão a serem vistos em enfermarias de oncologia conforme mais velhos (RC = 2,03 [1,98‐2,09]) ou caso morassem na região Sul (RC = 1,50 [1,29‐1,73]). Por outro lado, os tumores ósseos mostraram menor propensão a tratamento (redução da RC) em enfermarias de oncologia, independentemente da idade, sexo e região. Conclusão: Foi visto um risco elevado de tratamento, em enfermarias de oncologia, de pacientes mais velhos e os tratados na Região Sul. Os tumores ósseos foram, em geral, tratados em enfermarias de oncologia pediátrica, ao passo que os cânceres de pele foram tratados em enfermarias de oncologia médica, independentemente de idade, sexo e região. Keywords: Adolescents and young adults, Cancer, Site of care, Palavras‐chave: Adolescentes e adultos jovens, Câncer, Local de atendimento